A Review of the Impact of Institutions on Public Sector Efficiency - Alqasimi, Salem Abdulrahman; Zervopoulos, Panagiotis D.; Sharker, Abu Elias; Fousteris, Andreas E. (International Review of Management and Marketing, 2025)
This study integrates insights from governance studies, public choice theory, and institutional economics to examine how formal (e.g., rule of law, regulatory quality) and informal institutions (e.g., cultural norms) influence public sector efficiency. Specifically, it looks into how formal institutions— like the rule of law, regulatory quality, and corruption control- shape governance results—and informal institutions—like cultural norms and practices. From a methodological standpoint, the review critically assesses the measure and analysis of institutional effects on public sector performance using both quantitative techniques, such as Data Envelopment Analysis (DEA), Stochastic Frontier Analysis (SFA), Artificial Intelligence (AI), and Machine Learning (ML), as well as qualitative techniques, such as surveys and interviews. 90,643 academic publications were subjected to a bibliometric study, emphasizing fields such as environmental management, healthcare, and education. This review highlights the integration of AI and qualitative frameworks with traditional econometric models to deepen understanding of public sector efficiency. It also explores complex theories, such as the “grease the wheel” theory, which challenges the notion that corruption is universally harmful. The study identifies gaps in current research, including conceptual, data, and methodological limitations, and offers practical suggestions for future work. This analysis underscores the need for flexible and context-specific governance approaches by combining diverse methodologies and frameworks to present a unified view of the link between institutions and public sector efficiency.